UNDERGRADUATE STUDENTS’ ATTITUDES TOWARD ENGLISH WRITING AT ENGLISH STUDY PROGRAM IN JAMBI UNIVERSITY: SINTHYA PRALINDA, REKO HARY PUTRA. - Pralinda, Shintya; Hari Putra, Reko (Qawwam : The Leader's Writing, 2022)
The purpose of this research was to investigate the undergraduate students’ attitudes toward English writing in the English Study Program at Jambi University. This research was quantitative research with a survey approach through a questionnaire. The sample of this research was 43 third-semester students of Regular (classes A and B) chosen by using a total sampling technique. The data in this research were obtained through 18 questions of the questionnaire adopted from Ansarimoghaddam & Tan’s research (2014). The finding showed that undergraduate students’ attitudes toward English writing at the English Study Program in Jambi University are positive in the three components of attitudes (cognitive, affective, and behavior). From the all components, the average total mean distribution was 2.6137. Whereas from each component, like in cognitive aspects, the average of students’ responses was 2.5514. This aspect is defined as how capable someone is of the activity. Next, in the affective aspect, the average of students’ responses for this aspect was 2.6163. This aspect is defined as how the activities in English writing make the students feel. Last, in behavior aspects, the average of students’ responses was 2.6733. This aspect is defined as when the students need to determine how they should behave toward a certain thing, in this case English writing. It also talks about their experience with this thing.